To the place of no beginning: poems - Friedman, Jake, author; Beachy-Quick, Dan, advisor; Dungy, Camille T., committee member; Orsi, Jared, committee member (Colorado State University. Libraries, 2025)
To The Place of No Beginning: Poems is a collection of documentary poems exploring a critical history of the American West. Ranging from the Spanish Conquistas in the 15th century to the end of the so-called Indian Wars in the end of the 19th, my work seeks to excavate the founding injustices of America's colonial heritance. As documentary poems, each piece is composed of found text from primary historical sources, which is transcribed, broken down, and rearranged to create something new. In doing so, my goal is to turn the words of empire against itself—to enact some kind of critical, literary resistance, to perform a rhetorical analysis or deconstructive reading.
Keywords: poetry; documentary; West